Evaluation of genetic risk for Alzheimer's disease in the Hong Kong Chinese population: Genetics/genetic factors of Alzheimer's disease. (7th December 2020) - Zhou, Xiaopu; Chen, Yu; Lai, Nicole Chit Hang; Li, Yuen Tung; Kwok, Timothy C.Y.; Mok, Vincent C.T.; Zhang, Yulin; Ma, Shuangshuang; Liu, Saijuan; Chen, Yuewen; Tong, Estella Pui‐Sze; Ip, Fanny C.F.; et al.
Abstract: Background: Alzheimer's disease (AD) is a leading cause of mortality in the elderly. Although genome‐wide association studies (GWASs) have identified dozens of genetic risk factors in the Caucasian population, their associations with AD in the Chinese population have not been thoroughly investigated. Method: A TaqMan‐based single‐nucleotide polymorphism genotyping assay was implemented to evaluate Caucasian GWAS risk variants in a Hong Kong Chinese AD cohort ( n = 732). Logistic regression analysis was performed to examine the associations between these risk variants and AD, adjusting for age and gender. Result: Several Caucasian AD candidate loci including SORL1 (rs11218343) and ABCA7 (rs4147929) were associated with AD in the Hong Kong Chinese AD cohort. Conclusion: Known Caucasian AD GWAS candidates can contribute to AD risk in the Chinese population. This suggests that AD pathogenesis might share general mechanisms in both Asian and Caucasian populations.